Clinical characteristics and risk factors of microvascular involvement in primary antiphospholipid syndrome: a longitudinal single-center study in China. (November 2019) - Sun, Y; Zhao, J; Zhang, P; Wu, C; Jiang, N; Zhou, J; Zhang, S; Wu, Q; Wang, Q; Li, M; Zeng, X
Objectives: The objective of this study was to investigate risk factors of microvascular involvement and survival in Chinese patients with primary antiphospholipid syndrome. Methods: In this single-center, retrospective study, we enrolled 112 patients with a confirmed diagnosis of primary antiphospholipid syndrome who were admitted to Peking Union Medical College Hospital from January 2004 to December 2016. Demographic data, clinical characteristics, laboratory results, and follow-up records were collected. Results: A total of 112 patients with primary antiphospholipid syndrome were studied. Microvascular involvement was identified in 21 patients (18.75%). Patients with microvascular involvement experienced fewer episodes of arterial or venous thrombosis (28.6% vs. 84.6%) and a higher incidence of thrombocytopenia (85.7% vs. 54.9%), respectively. Low complement and elevated high-sensitivity CRP levels were observed more frequently in the microvascular group compared with the non-microvascular group (complement 38.1% vs. 18.7%; high-sensitivity CRP 71.4% vs. 31.9%, respectively). Anti-β2-glycoprotein I antibodies were more prevalent in patients with microvascular involvement than in patients without (66.7% vs. 33.0%, respectively). Multivariate logistic regression analysis revealed that thrombocytopenia (odds ratio = 4.523, 95% confidence interval 1.139–17.962), elevated high-sensitivity CRP levels (odds ratio = 6.385, 95% confidence interval 1.969–20.704), and anti-β2-glycoprotein I antibody positivity (odds ratio = 5.042, 95% confidence interval 1.555–16.352) were independent risk factors for microvascular involvement. A Kaplan–Meier analysis revealed that survival was significantly poorer in patients with microvascular involvement compared with patients without ( p = 0.0278). Conclusions: In addition to arterial and venous thrombosis, antiphospholipid syndrome can affect the microvasculature of select organs. It is thus important for clinicians to be aware that antiphospholipid syndrome-associated microvascular involvement has a unique pathogenesis and can be a life-threatening condition.